Analisis Resepsi Masyarakat Tentang Gaya Hidup Hedonisme Selebgram (Studi Netnografi Pada Followers Instagram Sisca Kohl) - Sere Simanjuntak; Ressi Dwiana; Ria Wuri Andary (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2023)
The increasing trend of society's activities, in which individuals compete to show themselves off and gain recognition on social media in the era of globalization, is a sign of hedonism. Hedonism is a behavior that is regarded as true if the person involved experiences pleasure and enjoyment on social media. This study aims to analyze the reception of society towards the hedonistic lifestyle displayed by influencer Sisca Kohl using the method of netnography. In this research, the researcher employs Stuart Hall's theory of reception analysis, encoding-decoding, and selects 6 (six) research informants. The findings of this study reveal that Sisca Kohl's followers, with different backgrounds, can be divided into 3 (three) categories. The first category is the Dominant Hegemonic Position, in which informants passively accept the hedonistic lifestyle displayed on Sisca Kohl's Instagram. The second category is the Negotiated Code Position, where informants accept Sisca Kohl's hedonistic lifestyle but critically consider the content of the media message in accordance with their personal context, values, and more critical perspectives. The third category is the Oppositional Code Position, where informants reject or oppose the hedonistic lifestyle portrayed by Sisca Kohl and develop alternative understandings that align with their own views and values.